Evaluation of Waiver Effects in Maryland, 1998-2000 - Smith, Cindy J. ([Verlag nicht ermittelbar], 2005)
The purpose of this research was to assist policymakers in determining if the targeted youths affected by the waiver laws passed by the Maryland legislature in 1994 and 1998 were being processed as intended. The waiver laws were enacted to ensure that a youth who was unwilling to comply with treatment and/or committed a serious offense would have a serious consequence to his/her action and, therefore, would be processed in the adult system. As a result of the legislation, four pathways of court processing emerged which created four groups of youths to study: at-risk of waiver (not waived), waiver, legislative waiver, and reverse waver. A variety of data sources in both the juvenile and adult systems were triangulated to obtain the necessary information to accurately describe the youths involved. The triangulation of data from multiple file sources happened in a variety of formats (automated, hardcopy, and electronic files) from a variety of agencies to compare and contrast youths processed in the juvenile and adult systems. The five legislative criteria (age, mental and physical condition, amenability to treatment, crime seriousness, and public safety) plus extra-legal data were used as a framework to profile the youths in this study. Many of the variables chosen to explore each domain were included in previous studies. Other variables, such as those designed to operationalize mental health issues (not defined by the legislation) were chosen to extend the literature and to generate the most complete profile of youths processed in each system. The study includes variables pertinent to the five legislative criteria in addition to demographic and family information variables such as gender, race, and socioeconomic status, information on school expulsions, school suspensions, gang involvement, drug history, health, and hospitalization.